Evaluasi Pengolahan Limbah Cair Domestik pada Instalasi Pengolahan Air Limbah di Kota Bogor - Iren Chaerunnisa; Okti Dinasakti Nurul Mentari (Jurnal Serambi Engineering, 2024)
The population growth in Bogor City is increasing every year, which can be seen from the population data from 2018 to 2022, increasing by 84,934 people with a population growth percentage of 2.07%. As the population grows, the demand for clean water will increase. This will also have an impact on the amount of domestic wastewater produced. In 2021, access to adequate sanitation in Bogor City will only be 75.35%, while it should reach 100% to achieve the SDG targets. Therefore, in order to achieve adequate sanitation, it is necessary to have a domestic wastewater treatment plant (WWTP) and assess IPAL so that the domestic wastewater produced can be safely discharged into the environment. A WWTP consists of several treatment units such as an intake building, an anaerobic pond, an aerobic pond, a facultative pond, a maturation pond and a sludge drying bed. The WWTP can be evaluated by comparing the effluent after treatment with quality standards, namely the Minister of Environment and Forestry Regulation No. 68 of 2016. The evaluation results show that several parameters still do not meet the quality standards for effluent to be discharged into the environment. These parameters are BOD and total coliform. Meanwhile, the percentage of TSS parameter removal was 57.14%, BOD 26.34%, COD 64.28%, Ammonia 69.88% and Total Coliform 99%.